2014
DOI: 10.1097/gme.0b013e3182a4690b
|View full text |Cite
|
Sign up to set email alerts
|

Association between the vaginal microbiota, menopause status, and signs of vulvovaginal atrophy

Abstract: Objectives The vaginal microbiota help protect the female genital tract from disease. We sought to describe the composition of the vaginal microbiota between pre-, peri- and postmenopausal women and to explore the association between the microbiota and vulvovaginal atrophy (VVA). Methods 87 women (age 35–60) were classified as premenopausal (n=30), perimenopausal (n=29) or postmenopausal (n=28) according to STRAW guidelines. Mid-vagina bacterial community composition was characterized by 16S rRNA gene analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
196
4
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(229 citation statements)
references
References 64 publications
21
196
4
8
Order By: Relevance
“…The classic description of the postmenopausal vagina is of an environment devoid of lactobacilli, with an elevated pH, although numerous studies show that a significant proportion of women maintain vaginal colonization with lactobacilli after menopause. 46 Between 40–80% of women develop vulvovaginal symptoms in menopause, 1,2,22 which can be a source of significant distress. 23 The etiology of these common symptoms is not well understood, which limits treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic description of the postmenopausal vagina is of an environment devoid of lactobacilli, with an elevated pH, although numerous studies show that a significant proportion of women maintain vaginal colonization with lactobacilli after menopause. 46 Between 40–80% of women develop vulvovaginal symptoms in menopause, 1,2,22 which can be a source of significant distress. 23 The etiology of these common symptoms is not well understood, which limits treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…While all postmenopausal women experience a drop in serum estradiol, not all lose vaginal lactobacilli. 3,4,6 Recent data have shown that free glycogen in vaginal fluid, which is liberated from epithelial cells by enzymes like α-amylase, is associated with Lactobacillus colonization in both pre- and postmenopausal women, suggesting glycogen may be a mediating factor for Lactobacillus presence. 7,8 In premenopausal women, serum estrogen levels were not correlated with free vaginal glycogen levels, but this relationship has not been examined in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Subject information was collected by having subjects complete a questionnaire. Exclusion criteria included pregnancy and menopausal or postmenopausal status, as these conditions are known to influence the composition of the vaginal flora (10,11). In addition, patients were excluded if they were positive for Chlamydia trachomatis, Neisseria gonorrhea, or Trichomonas vaginalis, as these infections can provoke cervical and/or vaginal inflammation, which could confound immunological analysis of BV.…”
mentioning
confidence: 99%
“…All postmenopausal women who had completed at least one year of menstruation free period were included. Women who did not give consent, those who had not attained menopause, those who were receiving hormone replacement therapy and those who were suffering from severe, debilitating illness were excluded [16,17].…”
Section: Methodsmentioning
confidence: 99%